CPLA2α reversibly regulates different subsets of cancer stem cells transformation in cervical cancer. (26th February 2020) - He, Yuchao; Xiao, Manyu; Fu, Hui; Chen, Lu; Qi, Lisha; Liu, Dongming; Guo, Piao; Chen, Liwei; Luo, Yi; Xiao, Huiting; Zhang, Ning; Guo, Hua
Abstract: Cervical cancer stem cells (CCSCs) are considered major causes of chemoresistance/radioresistance and metastasis. Although several cell surface antigens have been identified in CCSCs, these markers vary among tumors because of CSC heterogeneity. However, whether these markers specifically distinguish CCSCs with different functions is unclear. Here, we demonstrated that CCSCs exist in two biologically distinct phenotypes characterized by different levels of cytosolic phospholipase A2α (cPLA2α) expression. Overexpression of cPLA2α results in a CD44 + CD24 − phenotype associated with mesenchymal traits, including increased invasive and migration abilities, whereas CCSCs with cPLA2α downregulation express CD133 and show quiescent epithelial characteristics. In addition, cPLA2α regulates the reversible transition between mesenchymal and epithelial CCSC states through PKCζ, an atypical protein kinase C, which governs cancer cell state changes and the maintenance of various embryonic stem cell characteristics, further inhibiting β‐catenin‐E‐cadherin interaction in membrane and promoting β‐catenin translocation into the nucleus to affect the transcriptional regulation of stemness signals. We propose that reversible transitions between mesenchymal and epithelial CCSC states regulated by cPLA2α are necessary for cervical cancer metastasis and recurrence. Thus, cPLA2α might be an attractive therapeutic target for eradicating different states of CCSCs to eliminate tumors more effectively. Abstract : We provided a model in which cytosolic phospholipase A2α reversibly regulates the transformation of cervical cancer stem cells from the quiescent epithelial‐like to malignant mesenchymal‐like states by regulating the phosphorylation of PKCζ, which further inhibits β‐catenin‐E‐cadherin interaction in membrane and promotes β‐catenin translocation into the nucleus to affect the stem cell phenotype and metastasis in cervical cancer.